2010
DOI: 10.1111/j.1365-2591.2010.01803.x
|View full text |Cite
|
Sign up to set email alerts
|

Histological and histomorphometrical evaluation of furcation perforations filled with MTA, CPM and ZOE

Abstract: The periodontium adjacent to perforations filled with MTA and CPM exhibited clear evidence of re-establishment and thus better biocompatibility than ZOE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 37 publications
2
47
1
2
Order By: Relevance
“…In other words, we made 5 samples of ProRoot MTA and another 5 samples for Ortho MTA for heavy metal analysis, whereas in previous studies the experiment was performed with only 3 replicates (20,37). Considering that the increasing sample size could reduce the risk of incorporating bias into the data, our results could be considered to give more solid evidence than in previous studies (12)(13)(14)(15)(16)(17).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In other words, we made 5 samples of ProRoot MTA and another 5 samples for Ortho MTA for heavy metal analysis, whereas in previous studies the experiment was performed with only 3 replicates (20,37). Considering that the increasing sample size could reduce the risk of incorporating bias into the data, our results could be considered to give more solid evidence than in previous studies (12)(13)(14)(15)(16)(17).…”
Section: Discussioncontrasting
confidence: 51%
“…In addition, there are studies that reported the sealing ability or biocompatibility of MTA as endodontic sealers (8)(9)(10)(11)(12)(13)(14). Furthermore, as was suggested in the recent review article by Parirokh and Torabinejad (1), various biomaterials with biological activities similar to those of MTA, such as Bioaggregate (Innovative Bioceramix, Vancouver, BC, Canada) (15) and MTA Angelus (Angelus, Londrina, PR, Brazil) (16), have been introduced and have shown good biocompatibilities and sealing abilities.…”
mentioning
confidence: 99%
“…The periodontium adjacent to perforations fi lled with MTA and Endo CPM Sealer exhibited clear evidence of reestablishment and thus demonstrated better biocompatibility than zinc oxide-eugenol ( Fig. 3.4 ) [ 51 ]. Contaminations of lateral perforations can impair the healing process.…”
Section: Biocompatibilitymentioning
confidence: 97%
“…D, dentin. H&E (bar, 100 lm) (Reprinted with permission from da Silva et al [ 51 ] © 2010 International Endodontic Journal ) days and compared to DiaRoot BioAggregate. The materials were inserted into Tefl on tubes and implanted subcutaneously.…”
Section: Biocompatibilitymentioning
confidence: 99%
“…Materials resulting from this attempt are listed in Table 7.2 . [ 76 , 77 ] (+) [ 159 ] (+) [ 50 ] (+) [ 160 ] (−) [ 124 ] iRoot SP Sealer Calcium silicate based (unknown) (+) [ 181 ] (+) [ 179 ] (+) [ 61 , 178 ] (+) [ 23 ] MTA Fillapex MTA + salicylate resin + natural resin + silica nanoparticles + bismuth oxide + dehydrated calcium sulfate (+) [ 78 , 149 ] (+) [ 124 ] (+) [ 75 ] (+) [ 23 ] (−) [ 20 ] (−) [ 154 ] MTA [ 76 ]. Hydroxyl and calcium ions have also been shown to release from this cement similar to MTA, and therefore, they may act as an alternative root-end fi lling material [ 160 ].…”
Section: Mta-based Sealersmentioning
confidence: 99%